Mini Review of Glucose Detection Using Plasmonic Sensor - Salsabiila, Natasya; Morsin, Marlia; Nafisah, Suratun; Razali, Nur Liyana; Mahmud, Farhanahani; Tukiran, Zarina (Emerging Advances in Integrated Technology, 2023)
Glucose is a crucial compound in human life. Glucose has important roles in energy source production and overall brain health. In addition, it can be converted into other compounds essential for the growth, repair, and maintaining tissues throughout the body. Also, glucose becomes an indicator of diabetes, i.e., ill when the body can not produce insulin hormone properly. The poor management of diabetes can affect long-term complications that can significantly impact a person’s quality of life and may lead to disability or even premature death if not properly addressed. Thus, it is important to do glucose detection to stay within a healthy range. The common methods patients use are glucose meters and urine testing on the laboratory scale. This method has several areas for improvement, such as being invasive, needing experts, and requiring a long-time detection. Thus, researchers come into various alternative glucose detection such as chromatography, mass spectrometry, electrochemical, and plasmonic sensor. Chromatography for glucose detection is rarely used in recent years because of its complexity. Then, for mass spectrometry, it is also complicated for the result and maintenance. As for electrochemical methods, the disadvantage is that other electroactive components on the sample can be interfered with. Plasmonic sensors that utilize the Localized Surface Plasmon Resonance (LSPR) phenomenon are considered due to their advantage, i.e., non-invasive, real-time monitoring, and highly sensitive to surrounding medium change. Plasmonic sensors usually use components of light absorption, luminescence, fluorescence, Raman scattering, reflectance, and refractive index based on the nanoparticles used as sensing materials. Still, transmission and reflection are popular and widely applied. Furthermore, plasmonic sensors generally consist of instruments such as a light source, fiber optic, chamber to place substrate/analyte, spectrometer/detector, and computer. Besides, plasmonic sensors can produce different analytical characteristics suitable for different cases and tuned for the need because of the various sensing materials used. Hence, plasmonic sensors become a promising alternative method for glucose detection.